Rare manifestations of pediatric chronic myeloid leukemia: a case report on priapism and a literature Review - Budair, Rawan; Baqain, Laith; Rihani, Rawad (Frontiers in Oncology, 2025)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm characterized by uncontrolled myeloid cell proliferation and is primarily caused by a reciprocal chromosomal translocation [t(9;22)(q34;q11.2)]. Typical manifestations of CML include nonspecific constitutional symptoms such as fatigue, weight loss, night sweats, and abdominal discomfort due to hepatosplenomegaly. Although priapism is a rare but recognized complication of CML, it more often occurs in adults than in children. This case report describes an 11-year-old patient who experienced persistent priapism and hyperleukocytosis and ultimately received a CML diagnosis. Priapism in pediatric CML is a serious medical emergency requiring prompt medical and surgical intervention to prevent long-term complications, including the loss of erectile function. A literature review identified 19 pediatric cases of priapism associated with leukemia, 15 of which were attributed to CML. The cases varied in clinical presentation, treatment approaches, and outcomes, with management often involving a combination of aspiration, irrigation, leukapheresis, and chemotherapy. In most cases, priapism was resolved with these interventions, but some required additional measures, including shunt surgery. This review emphasizes the importance of early recognition and intervention to prevent complications in children with CML-associated priapism.